Evaluation of Lisfranc Injuries: How Involved is the First Tarsometatarsal Joint?. Issue 1 (January 2022) - Wong, Liam H.; Chrea, Bopha; Atwater, Lara C.; Meeker, James E.
Category: Midfoot/Forefoot; Trauma Introduction/Purpose: Lisfranc injuries are among the most debilitating injuries to the midfoot. Various classification systems have characterized the injury patterns with specific focus on the interval between the base of the second metatarsal and the medial cuneiform as well as the importance of the ligamentous structures of the midfoot. The medial ligamentous restraints of the first tarsometatarsal (TMT) joint and the bony involvement of these injuries remains unclear. Improved knowledge on how the first TMT joint is affected in Lisfranc injuries will provide information on how best to manage these injuries. Methods: We conducted a single institution review of all Lisfranc fractures from 2010 through 2020. Patients were identified by CPT codes. Hardcastle and Myerson Lisfranc injury classifications and computed tomography and radiograph characterizations of the first TMT joint were identified by three foot and ankle trained orthopaedic surgeons. Light's kappa statistics (mean weighted Cohen's kappa) evaluated inter-rater reliability of Lisfranc classifications. The effects injury mechanism and Lisfranc classification on the first TMT joint were further assessed using t-test, Mann-Whitney U, Fisher's exact test, and analysis of variance. Results: Of 71 patients with a Lisfranc injury, 62 (87%) had a sign of injury to the first TMT joint, which significantly varied by Lisfranc classification (P<0.001; Table). Light's kappa coefficient for inter-rater reliability was 0.46. A fragment of the first TMT articular surface was present in 39 patients (55%; median size=10mm) and a medial capsular avulsion fragment was seen in 28 patients (39%). A fracture was present in the medial cuneiform in 25 patients (35%) and in the first metatarsal in 18 patients (25%). Forty-nine patients (69%) had medial/lateral TMT joint incongruence (median overhang=4mm); 21 (30%) had dorsal/plantar incongruence (median overhang=6mm), which significantly differed by Lisfranc classification (P<0.02) and gender (Female=3.5mm; Male=7mm; P<0.03). Angulation of articular surfaces in the first TMT joint over 5 degrees on the transverse/antero-posterior plane occurred in 32 patients (45%) and in 12 patients (17%) on the sagittal/lateral plane, which significantly differed between Lisfranc classifications (P<0.03). Conclusion: Lisfranc injuries have great potential for long-term disability requiring careful screening and diagnosis. The overwhelming majority of Lisfranc injuries include damage to the first tarsometatarsal joint. This is the first study to our knowledge that characterizes this in detail. This study found that the most common patterns involving the first TMT joint included joint incongruity, capsular avulsion and articular surface fracture. A better understanding of injuries to the first TMT can help orthopaedic surgeons with diagnosis and management.